2007
DOI: 10.1002/bem.20342
|View full text |Cite
|
Sign up to set email alerts
|

Alimentary hyperlipemia of rabbits is affected by exposure to low‐intensity pulsed magnetic fields

Abstract: An experimental study was carried out in rabbits to investigate the effects of exposing rabbits to low-intensity pulsed magnetic fields (PMFs) on alimentary hyperlipemia. Thirty female white big ear rabbits were randomly divided into three groups. The normal group was fed with a standard chow diet and the other two groups (hyperlipid and magnetic) were fed with the chow diet supplemented with cholesterol, yolk powder and lard. The magnetic group was exposed to 15 Hz pulsed magnetic fields. After 8 weeks, level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
(22 reference statements)
1
10
0
Order By: Relevance
“…Nevertheless, the two studies also did not find statistically significant change for HDL-c level, which is inconsistent with our results. In addition, many animal studies also reported that exposure to EMF did not change the blood levels of TC (Celikozlu et al 2012;Kim et al 2006;Portet and Cabanes 1988;Smialowicz et al 1981;Torres-Duran et al 2007) or TG (Bahaoddini et al 2008;Elferchichi et al 2010;Hori et al 2012;Portet and Cabanes 1988;Torres-Duran et al 2007), while other studies found an increase in blood TC or TG (Smialowicz et al 1981), even a decrease in TC (Bahaoddini et al 2008;Bellossi et al 1998;Coskun and Comlekci 2010;Hori et al 2012;Luo et al 2007), TG (Bellossi et al 1998;Coskun and Comlekci 2010;Luo et al 2007) and HDL-c (Luo et al 2007). Methodological variations such as the difference of exposure conditions (e.g., resource type, frequency, intensity, duration, and continuity of EMF exposure), subjects' susceptibility, or detection methods may have given rise to such inconsistent findings across studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the two studies also did not find statistically significant change for HDL-c level, which is inconsistent with our results. In addition, many animal studies also reported that exposure to EMF did not change the blood levels of TC (Celikozlu et al 2012;Kim et al 2006;Portet and Cabanes 1988;Smialowicz et al 1981;Torres-Duran et al 2007) or TG (Bahaoddini et al 2008;Elferchichi et al 2010;Hori et al 2012;Portet and Cabanes 1988;Torres-Duran et al 2007), while other studies found an increase in blood TC or TG (Smialowicz et al 1981), even a decrease in TC (Bahaoddini et al 2008;Bellossi et al 1998;Coskun and Comlekci 2010;Hori et al 2012;Luo et al 2007), TG (Bellossi et al 1998;Coskun and Comlekci 2010;Luo et al 2007) and HDL-c (Luo et al 2007). Methodological variations such as the difference of exposure conditions (e.g., resource type, frequency, intensity, duration, and continuity of EMF exposure), subjects' susceptibility, or detection methods may have given rise to such inconsistent findings across studies.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, another human study reported that compared with radio relay station operators, significantly higher serum TC and LDL-c were found both in broadcasting station and TV station operators, with no change of serum TG and HDL-c (Vangelova et al 2006). In addition, many animal studies also reported that exposure to EMF could influence plasma or serum TC and TG, with few studies concerning serum LDL-c and HDL-c, but the results were inconsistent across studies (Bellossi et al 1998;Celikozlu et al 2012;Güler et al 2007;Hori et al 2012;Lahbib et al 2010;Lee et al 2006;Luo et al 2007;Portet and Cabanes 1988;Torres-Duran et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the prevention of hyperlipidemia might also prevent steroid-induced osteonecrosis. We consider that PEMF could prevent osteonecrosis because several studies have shown that it can decrease serum lipid levels [12,23]. Ishida et al [13] also found that PEMF did not affect bone marrow fat cell size and hypothesized that its preventative effect on steroid-induced osteonecrosis occurs via a mechanism independent of lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…PEMF has proven to be an effective noninvasive method in treating several diseases both experimentally and clinically during the past decades, such as cardiovascular disease, soft tissue injury, and skeletal system disorder [18,27,31]. However, little data to date have reported the possible impact of PEMF on DM and DM-induced bone complications.…”
Section: Discussionmentioning
confidence: 99%
“…1, the PEMF waveform consisted of a pulsed burst (burst width, 5 ms; pulse width, 0.2 ms; pulse wait, 0.02 ms; burst wait, 60 ms; pulse rise and fall times, 0.3 and 2.0 μs) repeated at 15 Hz. This waveform has been proved effective in the prevention and treatment of bone disorders and cardiovascular diseases by our research group for a long period of experiment [18,27].…”
Section: Pemf Treatmentmentioning
confidence: 99%